Generation Z and Sustainable Digital Consumption: Patterns, Challenges, and Potential in Indonesia - Avid Leonardo Sari; Diyah Ayu Amalia Avina; Irwandi; Tekat Sukomardojo; Endang Fatmawati (GoAcademica Research & Publishing, 2025)
The development of digital technology has fundamentally changed people's consumption patterns, especially among Generation Z, who live in a fast-paced and connected digital ecosystem. This phenomenon presents significant opportunities and challenges in efforts to encourage more sustainable consumption behavior amidst increasing dependence on technology. In Indonesia, the dynamics of Generation Z's digital consumption demonstrate a shift in values ​​that reflect the need for efficiency, personalization, and social responsibility in daily digital activities. The purpose of this study is to analyze the patterns, challenges, and potential of Generation Z in realizing sustainable digital consumption in Indonesia. This study uses a qualitative approach, relying on data obtained from previous research, academic publications, and relevant sources that describe the phenomenon of digital consumption among the younger generation. The collected data were analyzed in depth to identify the relationship between consumption behavior, sustainability awareness, and strategies that can be implemented to strengthen positive change. The results show that Generation Z has high digital awareness but still faces a gap between knowledge and practices of sustainability. The main challenges arise from the dominance of instant consumption culture, digital social pressures, and the lack of systemic support that encourages ethical consumption. Nevertheless, the level of digital literacy, collaborative spirit, and tendency to support socio-environmental values ​​​​are strong assets for this generation to become agents of change. With educational strategies, sustainable business innovation, and cross-sector collaboration, Generation Z has great potential to become a key driver of transformation towards a more conscious, inclusive, and sustainable digital consumption ecosystem in Indonesia